Expansão agrícola e as transformações ambientais no município de Pedro Afonso – Tocantins - Silva, Valdivino Veloso da (Universidade Federal do Tocantins, 2022)
This research mentions the agricultural expansion that took place in the municipality of Pedro Afonso between the years 1985 to 2020, with the objective of analyzing the modern agricultural expansion and the physical environmental transformations of the municipality. The methodology used was the use of bibliographic material and Remote Sensing, through satellite images, applying techniques for the elaboration of maps of land use and occupation, which allowed observing the advance of agriculture and the reduction of vegetation areas in the municipality. The images were from satellites, Landsat 5, TM sensor from 1985, 1995 and 2005, and from Landsat 8, OLI sensor from 2015 and 2020, obtained in the dry period between July and August. With the SPRING software, the processing was performed for the application of the RGB false-color (Red, Green and Blue) colored compositions, from three spectral bands of the Landsat 5 TM sensor (5-4-3) and the OLI sensor of the Landsat 8 (6-5-4). Then, the supervised classification of the images was carried out, which made it possible to identify and delineate the classes of Land Use and Occupation, which are: Forest Formations (Riparian Forest, Gallery Forest and Cerradão), Fire Scars, Water Bodies, Agriculture (Agriculture and Livestock), Countryside Formations (Campo Limpo and Campo Sujo), Urbanization and Reforestation. For the final composition of the thematic maps, the software QGIS 3.10.14 was used. As for the results, we have: For the year 1985, the classes: Countryside Formations and Forest Formations, totaling about 77.77% of vegetation, Agriculture with 9.34%, Bodies of Water 1.53%, Fire Scars 11.28% and Urbanization 0.09% of the area of the municipality. In 1995, the classes: Countryside Formations and Forest Formations, representing 69.77% of vegetation, Agriculture 20.44%, Water Bodies 1.18%, Fire Scars 8.53% and Urbanization 0.09% of the municipality. In 2005, the classes: Countryside Formations and Forest Formations, presented 59.81% of vegetation, Agriculture 31.86%, Water Bodies 1.23%, Fire Scars 7.01% and Urbanization 0.10% of the municipality area. In 2015, the classes: Countryside Formations and Forest Formations, totaled 50.77% of the vegetation, Agriculture 43.78%, Water bodies 1.58%, Fire Scars 3.47% and Urbanization 0.32% of the municipality. In the year 2020, the classes: Countryside Formations and Forest Formations, totaled 47.4% of vegetation, Agriculture 50.19%, Water Bodies 1.23%, Fire Scars 7.01% and Urbanization 0.10% of the municipality area. Among the various problems observed, I cite: Disordered growth of the urban fabric of the municipality; silting up of water bodies; Use of riparian forest areas to replace agriculture and ranches for leisure; Use of water for irrigation of the sugarcane crop; Use of industrial sugarcane residues; Pasture degradation; uncovered soils; Deforested and underused areas; Deforestation and forest fires/fires for the use of stump swiddens and planting of crops. Although technological advances in the field have enabled comfort and well-being, physical and economic, this is not reality for a large part of the local population, which is still plagued by hunger, lack of basic sanitation, drinking water, housing, health, education, and a large number of people do not even have the basics for their survival.